Advanced growth and multifunctional characterization of L-Threonine single crystals: comprehensive Insights from structural, Functional, Optical, Mechanical, Antibacterial and Thermal properties with potential in optoelectronics, photonics and Nonlinear - N. Rajasekar,; K. Balasubramanian, (The Bioscan, 2026)
High-quality Single crystals of an organic nonlinear optical (NLO) material were obtained at room conditions via the slow solvent evaporation technique. The crystalline structure and phase purity were established through PXRD studies. Fourier transform infrared (FTIR) spectroscopy was utilized to investigate the presence of characteristic functional groups and molecular interactions. In addition to optical transparency (%) and direct bandgap evaluation via UV-Vis spectroscopy, the refractive index, reflectance, optical conductivity, and extinction coefficient were analyzed to provide a comprehensive insight into the material’s optical characteristics. Morphological surface features were examined through scanning electron microscopy (SEM). The EDX spectra revealed the presence of constituent elements with a uniform distribution and no detectable impurities, indicating the chemical purity and compositional homogeneity of the material. Third harmonic generation in L-Threonine crystalline samples was studied using the Z-scan technique. The photoluminescence emission peak at 466 nm was observed, corresponding to a electronic transition of 2.66 eV. CHN analysis verified the elemental constituents of the material, revealing the expected percentages of carbon, hydrogen, and nitrogen, thereby indicating its chemical purity and stoichiometric consistency. Thermal properties associated with the sample was evaluated through differential thermal analysis (DTA) and derivative thermogravimetry (DTG), where the theromogravimetric (TG) was determined, and the kinetic parameters of decomposition were evaluated employing both the kissinger and broidos method. Antibacterial studies against S. aureus and E. Coli revealed no inhibitory activity, indicating that the material is inactive as a bioactive agent. 1H and 13C FT NMR analyses of the material confirmed the characteristic chemical shifts of α and β-Protons, methyl protons, carboxyl carbon, and hydroxyl-bearing carbon, consistent with its amino acid structure. The comprehensive results possesses favorable optical, thermal and mechanical properties, rendering it a suitable material for photonic, optoelectronic and Nonlinear-optical applications. Keywords W-H Plot, Functional, Morphological, Mechanical, Thermal parameters: Broidos and Kissinger methods, Antibacterial: E. coli and S. Aureus, Opto-electronics, Photonics and nonlinear optics.